A finite-difference method for stress modelling based on wave propagation. Issue 3 (8th February 2023) - Fan, Zhuo; Cheng, Fei; Liu, Jiangping; Han, Bingkai; Zheng, Yunpeng
SUMMARY: The determinations of detailed stress states are of great importance for various environmental and engineering investigations, which makes numerical stress modelling a key issue in many fields. We developed a new stress modelling method governed by elastic wave equations using finite-difference scheme. By introducing an artificial damping factor to the particle velocity in wave modelling, the proposed method is able to solve both the dynamic stress evolution and the static stress state of equilibrium. We validate the proposed method both in body force and surface force benchmarks in different scales. With the proposed method, we are able to substantially improve the modelling accuracy of models in unbounded domain by using the perfectly matched layer as the artificial boundary conditions. A 3-D concrete-faced rockfill dam model is further presented as a numerical example of practical investigation. The consistent results with the finite-element method further illustrate the proposed method's applicability. As a minor modification to wave modelling scheme, the proposed stress modelling method is not only accurate for geological models through different scales, but also physically reasonable and easy to implement for geophysicists.